Application of Problem Solving Learning Model on Row and Series Material at SMK Panca Budi - Nina Fadilah; Fitri Ayu; Mira Yosefa Siregar; Desi Ramadhani (International Journal of Multilingual Education and Applied Linguistics, 2024)
Effective teaching-learning activities are also supported by several aspects such as teaching methods, teaching strategies, learning models , and so on. In this study, we know the extent of the effectiveness of problem-solving learning compared to ordinary learning. Based on the research conducted, the results obtained that concluded the Problem-Solving learning mode proved effective in improving students' mathematical problem-solving abilities. Data analysis for this study used a t-test in this case obtained an average difference from the experimental class group given treatment using Problem-Solving learning and non-problem Solving class groups. The calculation results obtained a t count value (th) of 2.824 for the experimental class and 2.819 for the control class, with the table t value for db 68 sig 5% If consulted in the t table obtained 1.990 then based on the t-test criteria it can be concluded that the t value Count more than t table with GIS greater than SIG alpha by 5%, it can be concluded that count t > t table can be decided to test the hypothesis I that null hypothesis is rejected and alternative hypothethetics are accepted, in this case, there is a significant difference between students' mathematical problem-solving ability between the group of students taught using the Problem-Solving method and the group of students taught without using the Problem-Solving model.